ACSL1 Regulates TNFα-Induced GM-CSF Production by Breast Cancer MDA-MB-231 Cells - Thomas, Reeby; Al-Rashed, Fatema; Akhter, Nadeem; Al-Mulla, Fahd; Ahmad, Rasheed (Biomolecules (Basel, Switzerland), 2019)
Overexpression of granulocyte-macrophage colony-stimulating factor (GM-CSF) in different types of cancer is associated with tumor growth and progression. Tumor necrosis factor-α (TNFα) is involved in the induction of GM-CSF in different cells; however, the underlying molecular mechanism in this production of GM-CSF has not been fully revealed. Recently, it was noted that TNFα mediates inflammatory responses through long-chain acyl-CoA synthetase 1 (ACSL1). Therefore, we investigated the role of ACSL1 in the TNFα mediated production of GM-CSF. Our results showed that MDA-MB-231 cells displayed increased GM-CSF mRNA expression and secretion after incubation with TNFα. Blocking of ACSL1 activity in the cells with triacsin C markedly suppressed the secretion of GM-CSF. However, inhibition of β-oxidation and ceramide biosynthesis were not required for GM-CSF production. By small interfering RNA mediated knockdown, we further demonstrated that TNFα induced GM-CSF production was significantly diminished in ACSL1 deficient cells. TNFα mediated GM-CSF expression was significantly reduced by inhibition of p38 MAPK, ERK1/2 and NF-κB signaling pathways. TNFα induced phosphorylation of p38, ERK1/2, and NF-κB was observed during the secretion of GM-CSF. On the other hand, inhibition of ACSL1 activity attenuates TNFα mediated phosphorylation of p38 MAPK, ERK1/2, and NF-κB in the cells. Importantly, our findings suggest that ACSL1 plays an important role in the regulation of GM-CSF induced by TNFα in MDA-MB-231 cells. Therefore, ACSL1 may be considered as a potential novel therapeutic target for tumor growth.